Hydraulic jump below a sluice gate - Quek, Melvyn Zhiqian. (2011)
This project investigates how a hydraulic jump is formed when the 2-D rectangular jet exit is narrowed progressively so that 3-D jets of varying widths can be discharged into the downstream tailwater. This is equivalent to a 3-D jet flow into an expanded downstream channel. Therefore, this project investigates the effects of the channel expansion on the dissipative characteristics of the 2-D and 3-D hydraulic jump phenomenon.The outcomes of the experiments yielded some interesting explanations and analysis results. Firstly, as the channel gets narrower, the energy dissipated will tend to increase. Next, the hydraulic jump lengths as the channel narrows are relatively the same for the different channel widths used in this project. However, the conjugate depth ratios are considerably affected by the narrowing of the channel width. Smaller channel widths correspond with lower conjugate depth ratios and vice-versa. This means that the difference between the water levels at upstream and downstream of the hydraulic jump are getting closer as the channel gets narrower. It clearly means that when the channel is narrowed greatly, it will be much more difficult to get a visible and definite hydraulic jump due to the Y2 and Y1 values getting closer to each other. Finally, a proper hydraulic jump is tougher to be formed as the channel gets narrower and narrower.